Controlling multiple returnings in non-sequential double ionization with orthogonal two-color laser pulses - Ma, Xiaomeng; Zhang, Xiaofan; Tong, Aihong (Frontiers in Physics, 2023)
With the three-dimensional semiclassical ensemble model, we studied the nonsequential double ionization by orthogonal two-color laser pulses. Our calculations show that the proportion of events experiencing multiple returnings, the sum of the final energies of two electrons, and ion momentum distribution depend on the relative phase of the two-color fields, exhibiting oscillatory behavior with a period of π. Back analysis of these trajectories reveal that we can control the recollision energy of the electron by changing the relative phase of the two-color laser pulse. As a consequence, the trajectories of multiple-returning change with the relative phase, resulting in the relative-phase-dependent ion momentum distributions. The result shows the momentum distribution of the ions in the trajectories of multiple-returning are clearly wider than that for the case of single-returning. For the multiple-returning events, the binary recollision leads to smaller scattering angle of the first electron.